Investigation of cardiomyopathy using cardiac magnetic resonance imaging part 2: Rare phenotypes - O’Neill, Ailbhe C (Baishideng Publishing Group Co., Limited, 2012)
Cardiac magnetic resonance imaging (CMRI) has emerged as a useful tertiary imaging tool in the investigation of patients suspected of many different types of cardiomyopathies. CMRI images are now of a sufficiently robust quality to enable high spatial and temporal resolution image acquisition. This has led to CMRI becoming an effective non-invasive imaging tool for many cardiomyopathies. In this two-part review we outline the typical sequences used to image cardiomyopathy and present the imaging spectrum of cardiomyopathy. Part I focused on the current classification of cardiomyopathy, the basic CMRI sequences used in evaluating cardiomyopathy and the imaging spectrum of common phenotypes. Part II illustrates the imaging spectrum of the more rare phenotypes.